Penerapan Manajemen Strategik Dalam Implementasi Supervisi Kepala Sekolah Mi Al-Wathoniyah 5 Berdasarkan Instrumen Akreditasi Satuan Pendidikan Tahun 2020 - Mania, Majidah Aqifah; Nugraha, Mulyawan Safwandy (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study evaluates the performance of madrasahs in implementing various aspects of education contained in the education unit accreditation instrument and analyzes several strategic management recommendations. Through interviews and observations, the study analyzed several critical points in school management, such as the principal's competence in academic supervision, creative and innovative leadership, building harmonious relationships between the madrasah community, managing facilities and infrastructure, and financial management. The results showed several challenges faced by the madrasah in implementing the new curriculum, managing human resources, and developing facilities and infrastructure. Recommendations include improving teacher supervision and training, recruiting selective educators, allocating resources wisely, developing guidance and counseling services, and implementing an efficient time management system. Therefore, madrasahs can implement strategic management to improve the effectiveness and efficiency of the learning process and create a learning environment conducive to the development of students' potential.